Local Climate Heterogeneity Shapes Population Genetic Structure of Two Undifferentiated Insular Scutellaria Species - Hsiung, Huan-Yi; Huang, Bing-Hong; Chang, Jui-Tse; Huang, Yao-Moan; Huang, Chih-Wei; Liao, Pei-Chun (Frontiers in Plant Science, 2017)
Spatial climate heterogeneity may not only affect adaptive gene frequencies but could also indirectly shape the genetic structure of neutral loci by impacting demographic dynamics. In this study, the effect of local climate on population genetic variation was tested in two phylogenetically close Scutellaria species in Taiwan. Scutellaria taipeiensis, which was originally assumed to be an endemic species of Taiwan Island, is shown to be part of the widespread species S. barbata based on the overlapping ranges of genetic variation and climatic niches as well as their morphological similarity. Rejection of the scenario of ‘early divergence with secondary contact’ and the support for multiple origins of populations of S. taipeiensis from S. barbata provide strong evolutionary evidence for a taxonomic revision of the species combination. Further tests of a climatic effect on genetic variation were conducted. Regression analyses show nonlinear correlations among any pair of geographic, climatic, and genetic distances. However, significantly, the bioclimatic variables that represent the precipitation from late summer to early autumn explain roughly 13% of the genetic variation of our sampled populations. These results indicate that spatial differences of precipitation in the typhoon season may influence the regeneration rate and colonization rate of local populations. The periodic typhoon episodes explain the significant but nonlinear influence of climatic variables on population genetic differentiation. Although the climatic difference does not lead to species divergence, the local climate variability indeed impacts the spatial genetic distribution at the population level.